The Dichotomy of Science in the Perspective of History and the Views of Classical Scholars - Rakhmad Widodo; Arfan Mu’ammar (Civiliza Publishing, Indonesia., 2026)
This study examines the phenomenon of the dichotomy of knowledge in Islamic civilization, with a primary focus on the epistemological perspective of Al-Ghazali. In the historical development of Islam, knowledge was initially perceived as an integrated unity between religious and rational dimensions; however, external influences and the process of Western colonization led to the separation between religious sciences and secular sciences. This study aims to explain the historical roots of the knowledge dichotomy, to reexamine Al-Ghazali’s views on the integration of revelation and reason, and to analyze the impact of this dichotomy on contemporary Islamic education systems. The research employs a library research method with qualitative analysis of Al-Ghazali’s classical works and modern scholarly literature. The findings indicate that the accusation against Al-Ghazali as the initiator of the knowledge dichotomy is not entirely well-founded; rather, he emphasized the importance of integrating rational knowledge and revelation for the benefit of the Muslim community. This study also identifies ideas and models of integration between religious knowledge and science that are relevant in the modern era and formulates a new epistemological paradigm based on Al-Ghazali’s thought to bridge the crisis of knowledge dualism in contemporary Islamic education.